# If the roots of equation (c2 - ab) x2 - 2(a2 -bc) x + b2 -ac = 0 are equal, proove that either a=o, or a3+b3+c3 = 3abc.Pleasehelp to solve above question urgently.

Given, equation is:

(c 2 – abx 2 – 2 (a 2 – bcx + (b – ac) = 0

To prove: a = 0 or a 3 + b 3 + c 3 = 3abc

Proof: From the given equation, we have

a = (c2 – ab)

b = –2 (a 2 – bc)

c = (b 2 – ac)

It is being given that equation has real and equal roots

D = 0

b 2 – 4ac = 0

On substituting respective values of ab and c in above equation, we get

[–2 (a 2 – bc)]2 – 4 (c 2 – ab) (b 2 – ac) = 0

4 (a 2 – bc)2 – 4 (c 2 b 2 – ac 3 – ab 3 + a 2 bc) = 0

4 (a 4 + b 2 c 2 – 2a 2 bc) – 4 (c 2 b 2 – ac 3 – ab 3 + a 2 bc) = 0

a 4 b 2 c 2 – 2a 2 bc – b 2 c 2 + ac 3 + ab 3 – a 2 bc = 0

a 4 ab 3 + ac 3 –3a 2 bc = 0

a [a 3 + b 3 + c 3 – 3abc] = 0

a = 0 or a 3 + b 3 + c 3 = 3abc

• 277

For Ax2+Bx+C=0 to have equal roots, the determinant should be 0   (i.e B2-4AC=0)

Determinant for the given equation = 0

(-2(a2-bc))2-4(c2-ab)(b2-ac) = 0

4(a2-bc)2 = 4(c2-ab)(b2-ac)

(a2-bc)2=(c2-ab)(b2-ac)

a4-2a2bc+b2c2 = c2b2-ac3-ab3+a2bc

a4-2a2bc = -ac3-ab3+a2bc

a4+ab3+ac3-3a2bc = 0

a(a3+b3+c3-3abc)=0

So a= 0 or a3+b3+c3-3abc =0

i.e. a=0 or a3+b3+c3=3abc

Proved

• 46
What are you looking for?